THE EVIDENCE OF VIRUS-LIKE PARTICLES IN CRABS (Scylla sp.) ISOLATED FROM INSIDEAND OUTSIDE POND SHRIMP INFECTED WITH WHITE SPOT DISEASE - Hari Supraptp (Jurnal Sain Veteriner, 2003)
The crabs (Scylla sp.) were investigated for the contamination of Whitespot Baculovirus (WSBV) due to they lived inside and outside pond when the disease outbreak. The 6 samples of crabs, all of them were contaminated by WSBV with the founding of virus-like particles in hyperthrophied nuclei and cytoplasm. The size of virus-like particles is 65 ± 10 nm in diameter and 145 + 10 rim in length. We suggest that crabs has a big role in the transmitting the disease in pond an acting as a host for some crustacean virus. Key words : Crabs, Scylla sp., Whitespot Baculovirus